2020
DOI: 10.31053/1853.0605.v77.n3.27744
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de sífilis en un hospital de la provincia de Buenos Aires en 8 años

Abstract: Introducción La sífilis constituye un problema de salud mundial. Objetivo: establecer la prevalencia de sífilis y la distribución según estadio en pacientes asistidos en el Servicio de Dermatología de Junio 2010 a Junio 2018, y comparar las características epidemiológicas que pudieran influir en el aumento de la prevalencia. Métodos Estudio de cohorte retrospectivo de pacientes ≥ 15 años, con diagnóstico de sífilis adquirida. Para el análisis de los datos se consideraron dos periodos: P1: 2010-2015 y P2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Several studies corroborate this increase in Brazil and also in other countries in Latin America. 10 The number of syphilis cases in pregnant women may result from the increase in the number of cases per se, but also, in part, from the better availability of screening tests. Figueiredthe et al reported a directly proportional relationship between the diagnosis of maternal syphilis and the availability of rapid tests in primary care, as well as an inversely proportional relationship between the accessibility of treatment with Penicillin and cases of congenital syphilis.11 Accordingly, according to Ramos et al, when low rates of congenital syphilis are identified in association with high rates of syphilis in pregnant women in a given region, this may be related to accessibility to diagnostic serological tests and also to effective and timely treatment of pregnant women, with consequent prophylaxis of vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies corroborate this increase in Brazil and also in other countries in Latin America. 10 The number of syphilis cases in pregnant women may result from the increase in the number of cases per se, but also, in part, from the better availability of screening tests. Figueiredthe et al reported a directly proportional relationship between the diagnosis of maternal syphilis and the availability of rapid tests in primary care, as well as an inversely proportional relationship between the accessibility of treatment with Penicillin and cases of congenital syphilis.11 Accordingly, according to Ramos et al, when low rates of congenital syphilis are identified in association with high rates of syphilis in pregnant women in a given region, this may be related to accessibility to diagnostic serological tests and also to effective and timely treatment of pregnant women, with consequent prophylaxis of vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…En relación al nivel educativo alcanzado, la mitad de los casos positivos completó el nivel secundario y un 10% el universitario, mientras que los restantes continúan cursando en el secundario o superior, por lo que, la mayoría de los pacientes con sífilis tiene logrado un nivel educativo medio. En contraste con estos resultados, en un hospital de La Plata en el 2020 16 , se reportó un bajo nivel educativo con un 12% de pacientes con sífilis analfabetos o que no completaron el nivel primario de formación, mientras que en un estudio sobre VIH y sífilis realizado por el Ministerio de Salud de Córdoba 26 , el 41% de la población evaluada tenía estudios superiores, de los cuales el 31% había finalizado ese nivel de formación, asociando la infección a nivel de instrucción más alto.…”
Section: Discussionunclassified
“…Percebe-se que a sífilis vem aumentado ao longo dos anos, o que torna preocupante e traz à tona a dificuldade de prevenção e controle. As características sociais nos países em desenvolvimento assemelham-se nas características sociais de sua comunidade, a visto disso, um estudo de coorte realizado com mulheres maiores de 15 anos em Buenos Aires, identificou um aumento de casos nos casos de sífilis principalmente em relação as gestantes e puérperas (MIRAGLIA, 2020).…”
Section: Discussionunclassified